COVID-19 Outbreak Associated with Air Conditioning in Restaurant, Guangzhou, China, 2020 - Lu, Jianyun; Gu, Jieni; Li, Kuibiao; Xu, Conghui; Su, Wenzhe; Lai, Zhisheng; Zhou, Deqian; Yu, Chao; Xu, Bin; Yang, Zhicong (Emerging infectious diseases, 2020)
During January 26-February 10, 2020, an outbreak of 2019 novel coronavirus disease in an air-conditioned restaurant in Guangzhou, China, involved 3 family clusters. The airflow direction was consistent with droplet transmission. To prevent the spread of the virus in restaurants, we recommend increasing the distance between tables and improving ventilation.